Vihara Setia Budi, Kelenteng Persembahan Bagi Kwan Tie Kong - Repelita Wahyu Oetomo (Balai Arkeologi Sumatera Utara, 2010)
AbstractSetiabudi Vihara is a holy building for the people of adherent Tridharma teachings (Confucianism, Taoism and Buddhism), but more specifically, the Vihara is known as an offering to the Gods of Kwan Tie Kong. The procedure of worship and layout of space in this vihara followed the teachings of Confucianism; it is reflected from the ornaments that decorate the buildings and architecture.